Analisis Sistem Evaluasi Program Pendidikan Untuk Meningkatkan Efisiensi Manajemen Sekolah Dasar - Makki, Muhammad; Tahir, Muhammad; Nisa, Khairun; Syazali, Muhammad; Ibrahim, Ibrahim (Jurnal Ilmiah Profesi Pendidikan, 2025)
Effective program evaluation is a fundamental prerequisite for ensuring quality and accountability in primary education institutions. Consequently, this study aims to analyze the education program evaluation system in elementary schools to improve school management efficiency. The study focuses on three main aspects: identifying weaknesses in the existing evaluation system, analyzing the effectiveness of the evaluation instruments used, and providing strategic recommendations for improving the evaluation system to make it more focused and sustainable. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to principals, vice principals, teachers, and education personnel (tendik), with a total of 84 respondents. The results show that the existing education program evaluation system still faces various problems, including limitations in indicator standards, a lack of consistency in implementation, and minimal utilization of evaluation results for managerial decision-making. The evaluation instruments used are also not fully effective in describing program achievements, especially in qualitative aspects such as character development and student creativity. These findings emphasize the need to strengthen the evaluation system with clearer standards, comprehensive instruments, and optimal utilization of evaluation results in education program planning. Thus, this study concludes that improving the education program evaluation system in elementary schools is a crucial step in improving school management efficiency. The resulting recommendations can serve as a reference for principals, teachers, and policymakers in developing a more integrated, transparent, and needs-based evaluation system. Through appropriate evaluation, elementary schools can optimize resources, improve the quality of educational services, and support the sustainable achievement of educational goals.